Web Based Information System of Sales and Purchases on Cafe - R Fenny Syafariani; Defranata Defranata; Euis Neni Hayati (Jurnal Manajemen Informatika (JAMIKA), 2019)
At this time, the need for the use of computers in almost all aspects is needed, including in business and economics. Therefore, it takes a computerized system that can change the workings of a business process that was previously conducted manually in order to run better than ever. This information system will be implemented using object-oriented approach method and prototype development method, that is by listening to what client wants, then designing the program and revising when there is still less. This program uses a PHP programming language that makes the whole system computerized. The design of the system using UML (Unified Modeling Language) obtained after the observation and interview in the company. With the creation of a computerized system, is expected to help the company in improving the effectiveness and efficiency during the company's operational activities and provide good performance from all employees of cafe.